The Other Side of Reason - Žukauskaitė, Audronė (Sociologija. Mintis ir veiksmas, 1998)
The aim article is to develop a non-identarian critique of reason. The point of departure of the argument is a view that uniqueness of the Cartesian project lies not in privileging the principle of reason, but in privileging the subjective reason. The argument is developed by arguing that the preconditions of possibility of subjective reason are expressed in the logic of identity. Yet because of this the idea of reason becomes an ideology of reason: the philosophical principles of rationality turn into preconditions of ethical and political action. The author claims that because of interrelation between the philosophical idea reason and the institutions and structures of power, a critique of the idea of reason is necessary. Such a critique is developed in two directions: first, reason encompasses an irrational moment in its definition; second, irrationality itself is a notion of reason.
Keywords: reason; subjective reason; Other; principle of identity; irrationality; René Descartes